Early Retirement: A Meta-Analysis of Its Antecedent and Subsequent Correlates - Topa, Gabriela; Depolo, Marco; Alcover, Carlos-Maria (Frontiers in Psychology, 2018)
Early or voluntary retirement (ER) can be defined as the full exit from an organizational job or career path of long duration, decided by individuals of a certain age at the mid or late career before mandatory retirement age, with the aim of reducing their attachment to work and closing a process of gradual psychological disengagement from working life. Given the swinging movements that characterize employment policies, the potential effects of ER –both for individuals and society– are still controversial. This meta-analysis examined the relationships between ER and its antecedent and subsequent correlates. Our review of the literature was generated with 151 empirical studies, containing a total number of 706,937 participants, with a wide range of sample sizes (from N=27 to N=127,384 participants) and 380 independent effect sizes (ESs), which included 171 independent samples. A negligible ES value for antecedent correlates of early retirement (family pull, job stress, job satisfaction, and income) was obtained (which ranged from r = -0.13 to r = 0.19), while a fair ES was obtained for workplace timing for retirement, organizational pressures, financial security, and poor physical and mental health, (ranging from r =0.28 to r = 0.25). Regarding ER subsequent correlates, poor ESs were obtained, ranging from r =0.08 to r = 0.18 for the relationships with subsequent correlates, and fair ESs only for social engagement (r = -0.25). Examination of the potential moderator variables has been conducted. Only a reduced percentage of variability of primary studies has been explained by moderators. Although potential moderator factors were examined, there are several unknown or not measurable factors which contribute to ER and about which there are very little data available. The discussion is aimed to offer theoretical and empirical implications suggestion in order to improve employee’s wellbeing.